Ecosystem Restoration Policy in Production Forest and Its Implementation in Indonesia - Pareira, Maria Helena Yeni; Kartodihardjo, Hariadi; Bahruni (Jurnal Manajemen Hutan Tropika, 2020)
The issuance of the Ministry of Forestry Regulation (Number SK 159/Menhut-II/2004) on Ecosystem Restoration in Production Forest marked a paradigm shift in production forest management in Indonesia from timber to ecosystem-based. By 2019, the Ministry of Environment and Forestry (MoEF) has issued 16 ecosystem restoration concessions (ERC) in production forest totaling 622,826 ha, or only 21% out of the 3 million ha of MoEF’s target. Although this policy was considered a breakthrough and it garnered significant attention, currently, there is no comprehensive assessment on the development of ERC policy and its impacts on achieving MoEF’s target. Applied a combination of policy content, process, and implementation analysis, and rational policy analysis, this research examined the gaps in ER policy and implementation and identified policy space to pursue necessary policy improvement. The findings suggested that existing policy remains inadequate to support the implementation of ERC from the licensing process to performance evaluation. This study has identified the need to revise the applicability of regulations to facilitate the objectives of ERC as a management unit, and the objective of ecosystem restoration in the production forest. Revisions include ecological, social, and economic aspects using available policy space that supported by the coalition of actors within the Ecosystem Restoration Working Group.